Evaluating tourism potentials for site development tourism along River Ethiope, Abraka, Nigeria - Awaritefe, O. D.; Ejemeyovwi, Danny Ochuko (Journal of Sustainable Tourism and Entrepreneurship, 2020)
Purpose: The empirical research study evaluated environmental potentials of site locations for Tourism development along River Ethiope, Abraka Delta State, Nigeria, Four(4)sites’ 40 environmental features were considered important in the tourism sites evaluation. The primary data sources used include oral interview and administration of questionnaires. Research methodology: These are physical, biological and human components of tourism destinations, evaluated for each of the 4sites, and compared. Each of the 40 factors was measured using appropriate instruments like measuring tape and floater (for velocity). Students t test was undertaken to compare the evaluations of the two groups of professional and non-professional assessors. With a calculated value of 0.143, and table value of 0.283, with df2:3 at 0.05 level, the difference in site ranking between the first and second evaluation was not considered significant. High confidence or reliability can therefore be placed on the tourism site evaluation results obtained at the 0.05 significance level. The use of nominal or interval scales was to estimate variables, which were not subject to direct measurements in interval scale. Three groups of sites emerged from the preliminary survey of those selected: Natural or undeveloped sites, relate. Results: Result obtained showed that undeveloped and natural sites emerged most highly rated in environmental potentials for tourism site development compared to underdeveloped or highly developed sites. Limitation: The area lies within tropical equatorial rain forest vegetation which is an impenetrable ticket of under growth with trees and climbers. Moreover, dangerous reptiles especially (snakes and crocodile) as well as insect (Mosquitos and tsetse fly) are present and harmful to man in the environment. Contribution: The study concludes and suggests natural sites be accord priority in tourism site development along River Ethiope and invariably other related natural area worldwide for maximum patronage implications based on advocated research methodology. Keywords: Tourism, Site, Evaluation, Development, River Ethiope, Abraka